2021
DOI: 10.3389/fsurg.2021.604880
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram to Predict Long-Term Survival Outcomes of Patients Who Undergo Pneumonectomy for Non-small Cell Lung Cancer With Stage I-IIIB

Abstract: Background: In this study, we aim to establish a nomogram to predict the prognosis of non-small cell lung cancer (NSCLC) patients with stage I-IIIB disease after pneumonectomy.Methods: Patients selected from the Surveillance, Epidemiology, and End Results (SEER, N = 2,373) database were divided into two cohorts, namely a training cohort (SEER-T, N = 1,196) and an internal validation cohort (SEER-V, N = 1,177). Two cohorts were dichotomized into low- and high-risk subgroups by the optimal risk prognostic score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…LNR may reflect the patient’s tumor burden to some extent. Previous reports confirmed that LNR could be a predictive tool to evaluate the prognosis of non-small cell lung cancer patients ( 11 , 13 , 14 , 23 25 ). High-level LNR might be associated with the poor survival of those patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…LNR may reflect the patient’s tumor burden to some extent. Previous reports confirmed that LNR could be a predictive tool to evaluate the prognosis of non-small cell lung cancer patients ( 11 , 13 , 14 , 23 25 ). High-level LNR might be associated with the poor survival of those patients.…”
Section: Discussionmentioning
confidence: 68%
“…The examined lymph nodes (LNs) and lymph node ratio (LNR) were confirmed as the significant prognostic indicators for resected non-small cell lung cancers based on previous studies ( 11 14 ). LNR was defined as the ratio of the number of metastatic lymph nodes divided by the total number of dissected lymph nodes.…”
Section: Introductionmentioning
confidence: 53%
“…Finally, a nomogram was established. As is known that nomogram is a widely used and efficient tool for predicting prognosis in malignancies such as breast cancer [ 18 ], gastric cancer [ 19 ], esophageal carcinoma [ 20 ], and lung cancer [ 21 , 22 , 23 ]. The C-index of our nomogram was little pale (only 0.65).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evaluation of the prognoses for those patients remains important. Previous studies confirmed that nomograms had better performance in predicting prognosis than classic tumor, nodes, and metastasis (TNM) staging systems [ 12 , 13 ]. Therefore, this study aimed to construct a nomogram to improve the predictive ability for survival outcomes, and give clinical reference of adjuvant radiotherapy in postoperative SCLC patients with limited stage.…”
Section: Introductionmentioning
confidence: 99%